Differences in age and topographic distribution of the different histological subtypes of basal cell carcinoma, Taubaté (SP), Brazil - Flavia Regina Ferreira; Bruna da Costa Pevide; Rafaela Fabri Rodrigues; Luiz Fernando Costa Nascimento; Marcia Lanzoni de Alvarenga Lira (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: Basal cell carcinoma is the most common form of cancer in humans. OBJECTIVES: To identify the epidemiology of basal cell carcinoma in Taubaté-SP and verify a possible association between topography and the different histological subtypes of this tumor. METHODS: This was a cross-sectional study conducted at The University Hospital of Taubaté between 01/01/08 and 12/31/09. The study included patients with a confirmed diagnosis of basal cell carcinoma, of both genders, without age restrictions. The variables studied were incidence of basal cell carcinoma, topography, histological subtype, skin color, age and gender. We employed the chi-square test to identify the association between histological subtype and topography, and the student's t test to compare the mean age of onset for the different histological subtypes. RESULTS: The study included 239 individuals. The mean age of the sample was 68.0 years. Male subjects (57.7%) and whites (87.1%) predominated in the study. The predominant histological subtype was nodular (34.7%), followed by the superficial subtype. The most frequent sites of involvement were the head and neck (areas exposed to light), with predominance of the nasal region. The superficial subtype was an exception, as it showed a strong association with unexposed areas like the trunk. The mean age of onset of superficial basal cell carcinoma also differed from that of the other histological subtypes, 63.0 and 69.0 years, respectively. CONCLUSION: The results of this study suggest an association of the superficial histological subtype with younger patients and unexposed areas of the body, linking this type of tumor with a pattern of intermittent sun exposure, more similar to the standard photocarcinogenesis of melanoma.